Simulation of Normal Incidence Sound Absorption Coefficients of Perforated Panels With/Without Glass Wool by Transmission Line Parameters in a Two-Port Network - Nakai, Takayoshi (Rajshahi University Journal of Science and Engineering, 2016)
This paper describes simulation of normal incidence sound absorption coefficients of perforated panels by transmission line parameters in a two-port network. Maa and Sakagami have investigated micro perforated panels, MPP. But their theories can treat only near 1 % perforation rates of perforated panels with back cavities. If sound propagates as a plane wave, sound propagation can be represented as transmission line parameters in a two-port network. Perforated panels, back cavities, and glass wool absorption materials are represented as matrix of transmission line parameters, respectively. Transmission line parameters of a perforated panel with a back cavity are calculated as multiplication of their matrices. An input impedance can be calculated from the transmission line parameters. A normal incident absorption coefficient is calculated from the input impedance. Holes of the perforated panels have losses of viscous friction and thermal conduction at their walls. Simulations are done in the condition of 0.25 mm to 5 mm diameters of holes, 0.25 % to 25 % perforation rates, 0.5 mm to 5 mm thickness of the perforated panels with back cavities in which there are or are not glass wool absorption materials. The results of these simulations are good agreements with the results of our measurements by transfer function method except in the condition of more than 1 mm diameter of holes.